2011
DOI: 10.2133/dmpk.dmpk-10-rg-098
|View full text |Cite
|
Sign up to set email alerts
|

Profiling and Trend Analysis of Food Effects on Oral Drug Absorption Considering Micelle Interaction and Solubilization by Bile Micelles

Abstract: Correlation analysis between food effects on oral drug absorption (food effect) and physicochemical properties is important for efficient drug discovery and contributes to drug design. This study focused on micelle binding and solubilization considering bile micelles in the intestinal fluid. Profiling using about 40 launched drugs demonstrated that those in a high solubilization area (area 1) tended to have a positive food effect, and that drugs exhibiting negative/no food effect tended to coexist in a no/low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…In the epithelial membrane permeability limited (PL‐E) cases, a negative food effect can be observed. Bile micelle binding reduces the unbound drug concentration at the epithelial surface and reduces the effective permeability of a drug . In the solubility–epithelial membrane permeability limited (SL‐E) cases, Fa would not be increased by bile micelles.…”
Section: Food Effect Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the epithelial membrane permeability limited (PL‐E) cases, a negative food effect can be observed. Bile micelle binding reduces the unbound drug concentration at the epithelial surface and reduces the effective permeability of a drug . In the solubility–epithelial membrane permeability limited (SL‐E) cases, Fa would not be increased by bile micelles.…”
Section: Food Effect Predictionmentioning
confidence: 99%
“…Bile micelle binding reduces the unbound drug concentration at the epithelial surface and reduces the effective permeability of a drug. [42][43][44] In the solubility-epithelial membrane permeability limited (SL-E) cases, Fa would not be increased by bile micelles. The drug molecules bound to bile micelles cannot permeate across the epithelial cell membranes.…”
Section: Food Effect Predictionmentioning
confidence: 99%
“…BMS-F and BMS-H are examples of such compounds where it is generally thought that the physical entrapment of the drug in the viscous, post-prandial GI fluid milieu leads to unavailability of free drug for absorption through the paracellular junctions (29). Kawai et al (37) reported that hydrophilic drugs that dissolve rapidly are more likely to be limited by their permeation rates due to physical interaction with food components in the fed state. In this study, both BMS-F and BMS-H show rapid dissolution, although, the reason for reduced dissolution in FeSSIF was not investigated further.…”
Section: Case Studies On Fe Mechanismsmentioning
confidence: 99%
“…The former can be diagnosed by analytical techniques such as contact angle measurement for drug wettability. The latter can be tested for sequestration in bile, a situation for high log P drugs that show good bile micelle solubilization, but poor absorption at the epithelial surface due to unavailability of free drug (6,37).…”
Section: Limitations Of the In Vitro Models And Challengesmentioning
confidence: 99%
“…The extent of absorption of orally administered drugs with or without food appears to be determined by the drug's solubility and membrane permeability, among other parameters [1]. Administration of certain drugs with food has the potential to dramatically alter drug absorption, especially after meals with a high fat content [2].…”
Section: Introductionmentioning
confidence: 99%